Pengaruh Gaya Kepemimpinan dan Punishment terhadap Kinerja Karyawan pada PT. Multicentral Aryaguna Jakarta Timur - Ruli Muhamad Sopian; Susan Rachmawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
PT Multicentral Aryaguna is a subsidiary of Indomobil Group which is engaged in the field of building management and rental service sector. The purpose of this study was to determine the effect of leadership style and punishment on the performance of employees of PT Multicentral Aryaguna East Jakarta. In this study, researchers used statistica quantitative analysis, multiple linear regression analysis and coefficient of determination analysis with the help of SPSS 25 software. The sample used in this study was a saturated sample of 40 employees. The results of this study obtained using the t test that leadership style partialy has a positive and significant effect on employee performance with a significant level of 0.032 <0.05 and t test results of 2.226> 2.024. Punishment partialy has a positive and significant effect on employee performance with a significant level of 0.000 <0.05 and t test results of 4.992> 2,024. Leadership style and punishment simultaneously have a positive and significant effect with a significant level of 0.000 < 0.05 and F test results of 35.176> 3.25 on employee performance.